NEW HORIZON FOR AIPAN (FOLK ART OF UTTARAKHAND) MOTIFS THROUGH APPLIQUÉ - Negi, Monika; Rani, Anita; Singh, Anupriya (International Journal of Research -GRANTHAALAYAH, 2015)
The Indian folk arts with printing and embroidery play important role in creating new designs. Escalating demands of consumers requires modification in the fashion industry with respect to design, colour, style and technique.So an attempt was made to develop a design pool using folk art of Uttarakhand (aipan) for applique work. This also provides the opportunity to use the adapted traditional motifs on textiles and to preserve the beautiful traditional folk art. Aipan motifs were adapted for center design, border design, and buti design. Total thirty motifs / designs were developed keeping in mind their suitability for articles like bags, pencil purse and mobile holder. All the developed designs were subjected to visual evaluation for selection of two best designs in each category by the panel of thirty judges to find out the suitability of the developed designs for appliqué work. Thus total six motifs were selected for preparation of the five arrangements for each article. Four final selected arrangements with appliqué work were prepared using different embroidery stitches (slip hemming, couching, buttonhole and chain stitch). Plain red poplin and left-out fabrics were used to prepare articles. Finally articles were prepared by using selected arrangements and these prepared articles were highly appreciated by the consumers.